PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB), INFLASI DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP TINGKAT PENGANGGURAN JAWA TENGAH - Nurudin Nurudin; Ali Murtadho; Yeni Rahayu (Indonesian Journal of Thousand Literacies, 2023)
Unemployment has a lot of impact on economic, social, political and cultural life. Unemployment also curbs national development and the level of social welfare. Central Java as a province with the third largest population in Indonesia, with more than half of its population being the workforce, is also struggling to get rid of unemployment. The large population makes unemployment a separate problem in Central Java. This study aims to determine the effect of Gross Regional Domestic Product (GRDP), Inflation, and Human Development Index (HDI) on the unemployment rate in Central Java in 2010-2019. The data used is a time series, obtained from Statistics Indonesia (BPS). While the technical analysis used is multiple regression analysis. The results of this study show that GRDP has no significant effect on the unemployment rate in Central Java in 2010-2019, inflation has no significant effect on the unemployment rate in Central Java in 2010-2019, and HDI has a negative and significant effect on unemployment rate in Central Java in 2010-2019. Then simultaneously GRDP, inflation, and HDI have significant effect on the unemployment rate in Central Java in 2010-2019.